The use of LED radiation in the treatment of periodontitis - Danko, Е. М.; Kostenko, Є. Я.; Pantyo, В. В. (Actual Dentistry, 2024)
Topicality. Diseases of periodontal tissues are inflammatory diseases that are associated with the occurrence of dysbiosis of the microflora of the oral cavity with a predominance of periodontopathogenic microorganisms. Periodontitis leads to the destruction of periodontal tissues, the occurrence of bleeding gums, the formation of periodontal pockets and the loss of epithelial attachment to the gums. With the help of the main methods of treatment of periodontitis, it is not always possible to achieve the desired result, therefore the use of combined methods of treatment using low-intensity radiation is relevant. The aim of the work was to determine the effect of the led radiation on periodontal tissues and indicators of the index assessment of periodontal tissues, the papilla bleeding index and periodontal pocket depth in patients with chronic generalized periodontitis of the I–II degrees. Materials and methods. In this study, 50 patients with chronic generalized periodontitis of the I–II degrees were treated. The patients were divided into two groups: the 1st group consisted of 22 patients, who were treated according to generally accepted methods, and the 2nd group—28 patients, who were additionally irradiated with LED radiation in the red-infrared bands with wavelengths of 640±30 and 880±30 nm. The duration of irradiation was 20 minutes with a course of 10 procedures. The evaluation of the results of the treatment in both groups was determined using the PMA, Fedorov-Volodkina indices, the papilla bleeding index and the depth of the periodontal pockets was determined. Research results and their discussion. After the treatment, we got an improvement in all indicators in both groups. However, the periodontal tissue and periodontal pocket depth indices were significantly better in group 2 compared to group 1. After 6 months, the results of the PMA, Fedorov-Volodkina and papilla bleeding indices of group 2 were 30–62 .2% better than the indicators of group 1. The depth of periodontal pockets in patients of group 2 decreased on average by 1.26 mm, compared to the initial data before treatment, which is 20.7% better than the indicators of group 1, where the decrease in the depth of periodontal pockets occurred by 0.72 mm. Conclusions. Thus, LED radiation has a positive effect on the dynamics of hygiene indicators, an index assessment of the condition of periodontal tissues and the depth of periodontal pockets, due to its anti-inflammatory effect on periodontal tissues, and can be recommended for use in the complex treatment of periodontal tissue diseases. Keywords: LED radiation, low-intensity radiation, periodontal tissue disease, periodontitis, periodontal tissue index assessment, periodontal pocket, periodontal treatment.